Nonbonding Ammonium Stabilizing Manganese–Oxygen σ-Bond by Manipulating Spin Electrons to Regulate Enzymatic Activities - Qi Zhao; Min Zhang; Yixuan Gao; Lirong Zheng; Jin Ouyang; Na Na (Journal of the American Chemical Society, 2026)
Abstract The bonding strategy cannot effectively address the inherent limitations of layered nanozymes, resulting in their failure to maintain stability within the tumor microenvironment (TME). Herein, ammonium (NH4+)-intercalated δ-MnO2 nanozymes (N-MnO2) were constructed through the acid–base neutralization strategy. Due to interlayer van der Waals interactions, the NH4+ is stabilized in a nonbonded configuration. Significantly, nonbonding NH4+ exhibits unique electron-manipulating capabilities, enabling precise regulation of Mn 3d spin electrons from a high-spin state (t2g3eg1) to low-spin (t2g4eg0) configurations. The controlled spin-state redistribution prevents electron occupation in the eg antibonding orbitals (σ*), thereby significantly enhancing the stability of the Mn–O σ-bond and suppressing Jahn–Teller (J-T) distortions in the [MnO6] octahedra of layered MnO2. This dual nonbonding stabilization mechanism effectively resists structural disruption by endogenous glutathione (GSH, a scavenger of superoxide radicals), which can enhance the enzyme-mimetic activity. Furthermore, the nonbonding NH4+ in N-MnO2 maintains a dynamic Mn3+/Mn4+ equilibrium, endowing the nanozyme with dual catalase-like and oxidase-like activities. This can catalyze cascade enzymatic reactions (H2O2 → O2 → O2•–) to sufficiently enrich O2•–. Consequently, it is demonstrated that N-MnO2 possesses enhanced cascade catalytic performance within the complex TME for tumor-specific therapy.